A survey of lineage‐specific genes in Triticeae reveals de novo gene evolution from genomic raw material. (16th March 2023) - Poretti, Manuel; Praz, Coraline R.; Sotiropoulos, Alexandros G.; Wicker, Thomas
Abstract: Diploid plant genomes typically contain ~35, 000 genes, almost all belonging to highly conserved gene families. Only a small fraction are lineage‐specific, which are found in only one or few closely related species. Little is known about how genes arise de novo in plant genomes and how often this occurs; however, they are believed to be important for plants diversification and adaptation. We developed a pipeline to identify lineage‐specific genes in Triticeae, using newly available genome assemblies of wheat, barley, and rye. Applying a set of stringent criteria, we identified 5942 candidate Triticeae ‐specific genes (TSGs), of which 2337 were validated as protein‐coding genes in wheat. Differential gene expression analyses revealed that stress‐induced wheat TSGs are strongly enriched in putative secreted proteins. Some were previously described to be involved in Triticeae non‐host resistance and cold response. Additionally, we show that 1079 TSGs have sequence homology to transposable elements (TEs), ~68% of them deriving from regulatory non‐coding regions of Gypsy retrotransposons. Most importantly, we demonstrate that these TSGs are enriched in transmembrane domains and are among the most highly expressed wheat genes overall. To summarize, we conclude that de novo gene formation is relatively rare and that Triticeae probably possess ~779 lineage‐specific genes per haploid genome. TSGs, which respond to pathogen and environmental stresses, may be interesting candidates for future targeted resistance breeding in Triticeae . Finally, we propose that non‐coding regions of TEs might provide important genetic raw material for the functional innovation of TM domains and the evolution of novel secreted proteins.